The Impact of the Increase in Single Tuition Fees (UKT) on Access to Education at State Universities in Indonesia - Rahmania, Elvina; Sirozi, Muhammad (FKIP - Universitas Riau, 2025)
The Single Tuition Fee (UKT) policy is implemented as an effort to standardize education costs at state universities (PTN). This study aims to determine the impact of the increase in the Single Tuition Fee (UKT) on access to education at state universities in Indonesia. This study uses a literature study method by analyzing various relevant literature related to single tuition fees and access to education. The sources of data and information include various types of literature such as books, articles, magazines, websites, both Google Scholar, and publish or perish that are relevant to the research theme. The results of the study show that the increase in UKT has the potential to reduce access to education for students from low-income backgrounds. This can lead to a decrease in the number of prospective new students, widening the social gap, the financial burden on parents or students, and can result in students dropping out of college. For well-off families, the increase in UKT is not a problem where parents have a steady income, where only students from well-off families can access quality higher education. Meanwhile, for underprivileged families or those with mediocre or irregular incomes, it will be a big problem related to the increase in the single tuition fee. This also has an impact on life such as unemployment, crime and poverty will increase. Mental health due to stress and anxiety about the cost of education. The increasing cost of education in higher education is an obstacle for students who want to gain access to quality education.